Recognition and Cooperation Between the ATP-dependent RNA Helicase RhlB and Ribonuclease RNase E - Chandran, Vidya (J Mol Biol, 2007)
The Escherichia coli protein RhlB is an ATP-dependent motor that unfolds structured RNA for destruction by partner ribonucleases. In E. coli, and probably many other related γ-proteobacteria, RhlB associates with the essential endoribonuclease RNase E as part of the multi-enzyme RNA degradosome assembly. The interaction with RNase E boosts RhlB's ATPase activity by an order of magnitude. Here, we examine the origins and implications of this effect. The location of the interaction sites on both RNase E and RhlB are refined and analysed using limited protease digestion, domain cross-linking and homology modelling. These data indicate that RhlB's carboxy-terminal RecA-like domain engages a segment of RNase E that is no greater than 64 residues. The interaction between RhlB and RNase E has two important consequences: first, the interaction itself stimulates the unwinding and ATPase activities of RhlB; second, RhlB gains proximity to two RNA-binding sites on RNase E, with which it cooperates to unwind RNA. Our homology model identifies a pattern of residues in RhlB that may be key for recognition of RNase E and which may communicate the activating effects. Our data also suggest that the association with RNase E may partially repress the RNA-binding activity of RhlB. This repression may in fact permit the interplay of the helicase and adjacent RNA binding segments as part of a process that steers substrates to either processing or destruction, depending on context, within the RNA degradosome assembly.